Associations between sugar-sweetened beverage consumption, weight-adjusted-waist index, with psychological symptoms: a cross-sectional survey of adolescents in mainland China - Wang, Rui; Guo, Shihua; Yang, Guangyan; Li, Jun (Frontiers in Psychiatry, 2025)
BackgroundThe prevalence of psychological symptoms (emotional problems, behavioral problems, social adjustment difficulties) in adolescents continues to increase and has become a major concern in various countries. However, few studies have been conducted on the association between sugar-sweetened beverage (SSB) consumption, weight-adjusted waist index (WWI), and psychological symptoms in adolescents. The present study provides a reference for the prevention and intervention of psychological symptoms in Chinese adolescents.MethodsA multistage stratified whole cluster random sampling method was used to assess psychological symptoms, SSB consumption, weight, waist circumference, and demographic information in 44,675 adolescents aged 12-17 years in mainland China in 2023. The associations between SSB consumption, WWI, and psychological symptoms among adolescents were analyzed using logistic regression model analysis and ordered logistic regression analysis with the generalized linear model.ResultsThe prevalence of psychological symptoms among Chinese adolescents was 20.9%, with boys (21.4%) having a higher prevalence than girls (20.5%), and the difference was statistically significant (χ2 value of 5.687, P < 0.05). The proportion of adolescents with SSB consumption >4 times/week was 14.5%, and the WWI value was 9.36 ± 1.13. Ordered logistic regression analysis showed that, using SSB consumption <1 times/week and WWI quartile of Q1 as the reference group, adolescents with SSB consumption >4 times/week and WWI quartile of Q4 had the highest risk of developing psychological symptoms (OR=2.01, 95% CI:1.76-2.30) (P <0.001). The same trend was observed in boys (OR=1.67, 95% CI: 1.39-2.00) and girls (OR=2.68, 95% CI: 2.17-3.31) (P <0.001).ConclusionsThe prevalence of adolescent psychological symptoms is high in mainland China and is associated with SSB consumption and WWI. Effectively reducing SSB consumption and WWI plays a positive role in the prevention and intervention of adolescent psychological symptoms.